Differences in the gut microbiota of the black-faced spoonbill (Platalea minor) across different regions in China - Yang, Pengcheng; Bati, Habib; Feng, Erhui; Hu, Jingyao; An, Xian; Tan, Rongzeng; Dou, Xinyue; Chen, Taoyue; Tao, Yifan; Liu, Shuqiang; Yang, Liangliang (Frontiers in Microbiology, 2025)
The black-faced spoonbill (Platalea minor) is a critically endangered, first-class protected bird species in China, and its gut microbiota is thought to play a crucial role in the bird’s ecological adaptability. However, regional variations in the gut microbiota of this species remain poorly understood. We aimed to investigate how the gut microbiota of P. minor differs across distinct regions in China to identify key factors influencing its composition and function. Fecal samples from black-faced spoonbills were collected in four regions of China (Shenzhen, Dongfang, Danzhou, and Xinying). We performed high-throughput 16S rRNA gene sequencing and bioinformatics analyses to characterize the diversity and abundance of gut microbiota at various taxonomic levels (phylum and family). Across all regions, the gut microbiota of P. minor was dominated by the phyla Firmicutes and Proteobacteria. Nevertheless, significant regional differences in microbial composition and predicted functional pathways were observed. Notably, the Shenzhen population’s microbiota showed the highest diversity in pathways related to light and chemical energy utilization. In contrast, the Danzhou population’s microbiota exhibited a higher representation of pathways related to metabolism and cellular repair. These findings indicate that gut microbiota profiles differ substantially by region. Our results suggest that regional environmental and dietary factors shape the gut microbiota of P. minor, which in turn may influence the species’ ecological adaptation. This study provides new insights into the ecological adaptability of the black-faced spoonbill and offers a scientific basis for developing effective conservation and habitat management strategies for this endangered species.